We are all School - Sousa, A. N.; Couto, P. A. (Open Schools Journal for Open Science, 2020)
The project “We are all school” aimed to break down barriers between the school and the community, to convey the idea that we all have something to add to the school, as we are all educational agents. Our intention was to give more visibility to the activities that the school develops with the community in general. As this community is made up of people from different parts of the world, with diverse cultures and knowledge, we set out to look for their experiences and knowledge so that the school could benefit from the richness of this diversity. We also set out to involve the whole community more actively, valuing all the knowledge that could be carried to benefit the full learning path of students, regardless of their origin or social position.